The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3151/jact.15.328
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Fatigue Life Assessment of Damaged RC Decks -Data Assimilation of Multi-scale Model and Site Inspection-

Abstract: For estimating remaining fatigue life of RC bridge decks subjected to traveling wheel-type loads, presented is the data assimilation procedure, i.e., coupled life-span simulation with inspection data at site. Multi-scale analysis with hygro-mechanistic models is used for the platform of data assimilation on which the visual inspection of cracking on the members' surfaces and the acoustic emission (AE) tomography are numerically integrated. For verification, the wheel running load experiments of slabs were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Data assimilation analysis with the initial cracking by the pseudo-cracking starts in the middle of lifetime and it should coincide with the referential analysis for practical purpose. Tanaka et al (2017) also illustrated the strain fields of 3D extent which successfully converged to the true solution as well as the deflection by means of the predictor-corrector method.…”
Section: Data Assimilation By Pseudo-cracking Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Data assimilation analysis with the initial cracking by the pseudo-cracking starts in the middle of lifetime and it should coincide with the referential analysis for practical purpose. Tanaka et al (2017) also illustrated the strain fields of 3D extent which successfully converged to the true solution as well as the deflection by means of the predictor-corrector method.…”
Section: Data Assimilation By Pseudo-cracking Methodsmentioning
confidence: 94%
“…More detailed verification of pseudo-cracking method was conducted by Tanaka et al (2017) with non-ASR slabs having the same dimension as the one in this study. Figures 18 and 19 show the evolution of center deflection with both linear and logarithmic scales, in which we see the zig-zag deflection at unload and re-loading of 94 kN.…”
Section: Data Assimilation By Pseudo-cracking Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the responses of the real-scale RC slabs studied by Maeshima et al (2016) were referred for verification and validation processes of the proposed model. Then, the authors developed a data assimilation procedure to combine the multi-scale analysis with visual site inspection data by extending the pseudo-cracking method for RC bridge decks (Fujiyama et al 2013;Tanaka et al 2017) to the case of ASR damages. In the result, it was shown that ASR expansion could enhance the fatigue life of RC slabs.…”
Section: Introductionmentioning
confidence: 99%